Two autopsy cases of pulmonary leukemic infiltration mimicking severe pneumonia in patients with acute myeloid leukemia. (2021) - Iizuka, Hiroko; Mori, Yosuke; Fukuda, Yasutaka; Iwao, Noriaki; Koike, Michiaki; Noguchi, Masaaki
Highlights: Diverse pulmonary complications are often observed in acute myeloid leukemia. Clinically significant leukemic infiltration is rarely recognized antemortem. Autopsy revealed leukemic infiltration in patient mimicking severe pneumonia. It may be difficult to achieved accurate diagnosis without pathological examination. Non-invasive examinations for leukemic infiltration diagnosis are required. Abstract: Although a previous autopsy series demonstrated that pulmonary leukemic infiltration (PLI) is a major pulmonary complication in patients with acute myeloid leukemia (AML), an antemortem diagnosis of PLI is rare. Diverse pulmonary complications cause acute respiratory failure (ARF) in patients with AML undergoing chemotherapy. This article reports two elderly patients with AML who presented with ARF due to PLI mimicking severe pneumonia during induction chemotherapy. Accurate antemortem diagnosis of PLI was almost impossible without pathological examination since the clinical course was not typical of PLI. We recommend considering PLI in patients with AML who have an unknown etiology of ARF.